Management of the Al-Qur'an Literacy Program in Creating Tahfidz Learners - Sri Handayani; Aan Hasanah; Ahmad Zaldi; Abdul Karim; Jalaludin; Sahlan (Nidhomul Haq : Jurnal Manajemen Pendidikan Islam, 2025)
Indonesia is a Muslim country with a total of 87% of the population being Muslim, but data from the Ministry of Religion of the Republic of Indonesia in 2020 shows that the number of Al-Qur'an memorizers (Hafidz 30 Juz) in Indonesia is only around 30,000, about 0.01% of the total population of Indonesia. This study aims to analyze the management of the Al-Qur'an literacy program in creating tahfidz students at SMP Negeri 1 Cirebon City. This research uses a qualitative approach with a case study method and nonprobability sampling technique, purposive sampling data source collection techniques carried out by observation, interviews, and documents. Data validity testing is carried out with credibility, transferability, dependability, and confirmability tests. Data analysis includes data reduction, data presentation, and conclusions. The results of this study indicate that the management of the Qur'an literacy program by implementing the POAC theory put forward by Terry proved to be very effective. The effectiveness of the program in proving to be able to create tahfidz students at SMP Negeri 1 Cirebon City began to be carried out since 2016 well with the achievement of the target of passing tahfidz 40 students in 2023. Based on this, this research is expected to provide implications for managers of other educational institutions that to create students who memorize the Qur'an does not have to form an integrated Islamic school or include Qur'an learning into the local content curriculum. But simply with the right management concept, extracurricular programs can also implement tahfidz programs well and can produce graduates who are at least literate in the Qur'an and can even become memorizers of the Qur'an.